Does exercise have a preventive effect on secondary lymphedema in breast cancer patients following local treatment: a systematic review - Baumann, Freerk T.; Wiskemann, Joachim (Breast care, 2018)
Background: Secondary lymphedema (SL) is a possible side effect of breast cancer treatment. Current data describe a positive influence of exercise on upper lymphedema. This systematic review evaluates studies examining a potential preventive effect of exercise on SL incidence. Methods: A systematic literature search of PubMed, LIVIVO, and the Cochrane Library was performed. Results: 8 randomized controlled trials were included in the review. 3 studies investigated the effect of strength training, and 5 the effect of combined exercise therapy. 5 studies included participants without lymphedema at study entry, and 3 studies included both patients with and without lymphedema. The partly significant results showed that progressive strength training as well as combined dynamic exercise therapies consisting of physiotherapy, physical therapy, and/or kinesiotherapy are safe and can prevent SL. Onset as well as diagnosis of lymphedema were significantly decreased in 5 studies in the exercise group. Conclusion: All 8 studies included indicate a potential preventive effect of exercise on SL; however, further research is needed.
Gesehen am 06.03.2020